2005
DOI: 10.1016/j.cell.2005.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Cotranscriptional Set2 Methylation of Histone H3 Lysine 36 Recruits a Repressive Rpd3 Complex

Abstract: The yeast histone deacetylase Rpd3 can be recruited to promoters to repress transcription initiation. Biochemical, genetic, and gene-expression analyses show that Rpd3 exists in two distinct complexes. The smaller complex, Rpd3C(S), shares Sin3 and Ume1 with Rpd3C(L) but contains the unique subunits Rco1 and Eaf3. Rpd3C(S) mutants exhibit phenotypes remarkably similar to those of Set2, a histone methyltransferase associated with elongating RNA polymerase II. Chromatin immunoprecipitation and biochemical experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
812
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 741 publications
(864 citation statements)
references
References 84 publications
50
812
2
Order By: Relevance
“…3). Based on the recent evidence that Set2p-mediated methylation of H3K36 is involved in the recruitment of a repressive Rpd3 complex (35)(36)(37), the simplest explanation of these observations is that this complex negatively regulates both meiotic recombination and transcription. This negative regulation is likely to be a consequence of a closed chromatin structure caused by Rpd3p-mediated deacetylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Based on the recent evidence that Set2p-mediated methylation of H3K36 is involved in the recruitment of a repressive Rpd3 complex (35)(36)(37), the simplest explanation of these observations is that this complex negatively regulates both meiotic recombination and transcription. This negative regulation is likely to be a consequence of a closed chromatin structure caused by Rpd3p-mediated deacetylation.…”
Section: Discussionmentioning
confidence: 99%
“…HIS4 hotspot in wild-type, set2, rpd3, and set2 rpd3 strains Loss of the Rpd3p deacetylase results in increased acetylation of many sites in H3 and H4 histones (56,57), whereas loss of the Set2p methylase directly affects only methylation of H3K36 (34). The Set2p-mediated methylation, however, helps recruit a repressive Rpd3p-containing complex to chromatin, and elevated histone acetylation was observed for several loci in set2 mutant strains (35,37). Consequently, we examined the histone acetylation levels at H3K27 by chromatin immunoprecipitation (ChIP analysis) in the diploids FX1 (wild-type), JDM1093 (set2), JDM1095 (rpd3), and JDM1096 (set2 rpd3).…”
Section: Measurement Of Meiosis-specific Dsbs At Thementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in yeast have shown that methylation of H3-K36 by SET2 recruits histone deacetylase to transcribed regions and links to phosphorylation of the C-terminal domain of RNA polymerase II and the process of transcriptional elongation (Carrozza et al, 2005;Joshi and Struhl, 2005;Keogh et al, 2005). Of interest, Carrozza et al reported that the histone deacetylation occurs at coding regions and suppresses intragenic transcription.…”
Section: Functions Of Jumonji Family Proteins In Transcription and Chmentioning
confidence: 99%
“…Several important predictions arising from this E-MAP for novel gene functions have recently been studied and confirmed (10)(11)(12)(13)(14)(15)(16)(17). One such prediction was a connection between SET2, a histone methyltransferase, and Rpd3C(S), a histone deacetylation complex that contains the chromodomain protein Eaf3p as well as Rco1p.…”
Section: Introductionmentioning
confidence: 79%